ANTIBACTERIAL ACTIVITY TEST OF Liosina paradoxa SPONGE EXTRACT FROM POOPOH COASTAL WATERS, MINAHASA REGENCY - Pantow, Vania Consuella (PHARMACON, 2024)
Liosina paradoxa  sponge contains an active compound that can act as an antibacterial. This study aims to determine the antibacterial activity of the ethanol extract of Liosina paradoxa  on the growth of Staphylococcus aureus and Pseudomonas aeruginosa. The research was conducted using an experimental method. Extraction uses the maceration method to extract the active compounds from the Liosina paradoxa  sponge. The extraction results were tested to determine whether there was antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa; the test used the Kirby-Bauer agar diffusion method. The results of the test showed that there was antibacterial activity marked by the presence of an inhibition zone around the disc paper of the extract test solution on Staphylococcus aureus bacteria with a medium inhibition zone diameter of 7.25 mm and Pseudomonas aeruginosa bacteria with a medium inhibition zone diameter of 8.25 mm.